2021
DOI: 10.7759/cureus.20684
|View full text |Cite|
|
Sign up to set email alerts
|

Lemierre’s Syndrome: A Case of Life-Threatening Infection From Family Medicine Practice

Abstract: The use of antibiotic therapy has led to a major transformation in medicine with a substantial reduction in mortality. Due to the adverse effects associated with inappropriate antibiotic use, antibiotic stewardship interventions have been promoted to improve antibiotic prescription. However, delayed antibiotic therapy, when clinically needed, may result in increased morbidity. Here, we report the case of a previously healthy young man with an untreated acute upper respiratory infection for two weeks, who prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Tis perspective is also refected in the only retro-perspective study available that studied about 700 cases of LS from 2000 to 2017 and concluded that there are no disease-specifc elements of concern regarding the safety of anticoagulation in LS [12]. From our analysis of 26 LS cases from 2016 to 2021, anticoagulation was used in 76% of cases and the average duration was 9.8 weeks (ranging from 1 week to 16 weeks; Table 2 [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][41][42][43][44]. In our case, due to the absence…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis perspective is also refected in the only retro-perspective study available that studied about 700 cases of LS from 2000 to 2017 and concluded that there are no disease-specifc elements of concern regarding the safety of anticoagulation in LS [12]. From our analysis of 26 LS cases from 2016 to 2021, anticoagulation was used in 76% of cases and the average duration was 9.8 weeks (ranging from 1 week to 16 weeks; Table 2 [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][41][42][43][44]. In our case, due to the absence…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the duration of antibiotics, Riordan, 2007, referenced an estimate of 9 to 84 days with an average of 42 days [2]. We have analyzed 26 cases of LS from 2016 to 2021, and the average antibiotics duration was 5.3 weeks (Table 2) [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][42][43][44]. In clinical practice, due to the lack of an established guideline, the duration and selection of antibiotics highly varied based on clinical responses in patients.…”
Section: Discussionmentioning
confidence: 99%